Pengaruh Penggunaan Obat Antihipertensi Terhadap Sindroma Mata Kering di Surabaya - WISNU TRI PAMUNGKAS; INDIRA R. A; IRMA A. PASARIBU (HANG TUAH MEDICAL JOURNAL, 2020)
Abstract Background: Hypertension prevalence in Indonesia is increasing to reach 25.8% in the population aged 18 years and over. Amlodipine is one of the drugs for hypertension therapy which is included in the Calcium Channel Blocker (CCB) class. The use of antihypertensive medication itself is one of the risk factors that cause dry eye syndrome. Purpose: This study aims to determine the effect of the use of antihypertensive drugs on dry eye syndrome in patients with hypertension at Jagir Public Health Center in Surabaya working area. Methods: This study was an observational analytic study with a cross-sectional method. The subjects in this study were 48 respondents found divided into 2 groups namely, the group taking antihypertensive drugs> 6 months and not taking medication. The DEQ-5 questionnaire was completed and Schirmer I was examined. Results: Descriptive analysis of the Schirmer I test for the frequency of dry eye syndrome was higher in respondents who took antihypertensive drugs than those who did not take antihypertensive drugs. The results of statistical analysis using the chisquare test of significance that is equal to <0.001 or it can be said that p <α (0.05), indicates there is an effect of antihypertensive drug administration on dry eye syndrome based on the Schirmer test in hypertension patients at Jagir Public Health Center in Surabaya.. Conclusion: The use of antihypertensive drugs has an effect on dry eye syndrome in patients with hypertension at the Jagir Public Health Center in Surabaya